The Role of Bromelain and Papain Proteolytic Potential Binding to Crystalline P23T Γd Protein in Congenital Cataracts - Nugraha Wahyu Cahyana (International Journal of Pharmaceutical and Bio Medical Science, 2024)
Background: Congenital cataracts can cause permanent vision loss. The etiology of congenital cataracts varies widely. The exact etiology can’t be identified, but usually there an autosomal dominant inheritance. Objective: To assess the proteolytic potential of Bromelain and Papain enzymes against Crystalline P23T γD. Methods: This study is a pre-experimental study with a computer-based one shot case study approach. Papain enzyme data using 9PAP code and bromelain enzyme data using 1BI6 were obtained from the National Center of Biotechnology Information database (NCBI: www.ncbi.nlm.nih.gov/). Assessment of the proteolytic potential of Bromelain and Papain enzymes against Crystalline P23T D data using 2KFB code cluspro www.cluspro.bu.edu/home.php and data analysis. Results: The binding affinity of bromelain is -735.1 KCal/Mol and papain is -730.4 KCal/Mol. Conclusion: The bromelain enzyme has a lower binding affinity value than the papain enzyme, so it has the ability to form stable bond to the crystalline P23T D protein better than papain enzyme.